David Couper: beyond the badge : reflections of an ex-cop - Zaleski, Rob (Little Creek Press, 2022)
"When he stepped down in 1993 after 21 contentious, but highly successful years as the police chief in ultra-liberal Madison, Wisconsin, David Couper was widely regarded as one of the most influential law enforcement officials in Wisconsin's history. But little was known about his private life--or what motivated him to transform a paramilitary-type department into one that emphasized community relations; and to hire a large number of women and people of color, dramatically changing the complexion of the department. In 2020--nearly three decades after his shocking decision to resign and become an Episcopal priest--the former Marine met with award-winning columnist Rob Zaleski for a series of lively and provocative interviews that lift the veil on his private life and explain for the first time the reasons behind his many controversial decisions. He also talks about his unstable upbringing in the Twin Cities, the personal tragedies he's endured, and his evolution into one of the most inspiring human rights activists Wisconsin has known."--Publisher